Effect of Moisture Content and Normal Impact Velocity on the Coefficient of Restitution of ‘Memory’ Wheat Grains - Jacek Marcinkiewicz; Grzegorz Waldemar Ślaski; Mikołaj Spadło (Applied Sciences)
This study analyses the dynamic impact between winter wheat grains (‘Memory’ cultivar) and a flat metal surface under normal collisions. Four moisture levels (7%, 10%, 13% and 16%) and impact velocities from 1.0 to 4.5 m·s−1 were chosen to reflect conditions in agricultural machinery. A custom test rig—comprising a transparent drop guide, a high-sensitivity piezoelectric force sensor and a high-speed camera—recorded grain velocity by vision techniques and contact force at 1 MHz. Force–time curves were examined to evaluate restitution velocity, the coefficient of restitution (CoR) and the effect of moisture on elastic–plastic deformation. CoR decreased non-linearly as impact velocity rose from 1.0 to 5.0 m·s−1, and moisture content increased from 7% to 16%, falling from ≈ 0.60 to 0.40–0.50. Grains with higher moisture struck at higher velocities showed greater plastic deformation, longer contact times and intensified energy dissipation, making them more susceptible to internal damage. The data provide validated reference values for discrete element method (DEM) calibration and will assist engineers in designing grain-handling equipment that minimises mechanical damage during harvesting, conveying and processing.